Mental Health Outcomes of Healthcare Providers During COVID-19 Pandemic in Saudi Arabia: A Cross-Sectional Study - Sultana A. Alhurishi; Khalid M. Almutairi; Jason M. Vinluan; Ahmad E. Aboshaiqah; Mohammed A. Marie (Frontiers Media S.A., 2021)
Objective: In this descriptive cross-sectional study we aimed, to assess the level of depression, anxiety, insomnia and distress symptoms experienced by healthcare providers during the COVID-19 pandemic in Saudi Arabia.Methods: All healthcare providers currently working in different hospitals were invited to participate in this study. Data gathering started in March 2020 to May 2020. The participants answered a five-part questionnaire which includes demographic data, a 9-item Patient Health Questionnaire, a 7-item Generalized Anxiety Disorder, a 7-item Insomnia Severity Index, and a 22-item Impact of Event Scale-Revised, which assess the level of depression, anxiety, insomnia, and distress.Results: Out of 200 healthcare providers, 40% were males. 52% were aged 31-40 years old, 61% were married. The majority of the participants were Saudi nationals (84%), 74% were nurses, 11% were physicians and 15% were other healthcare providers. More than half of the participants worked as front-liners (57%). Overall, 73, 69, 62, and 83% of all healthcare providers reported symptoms of depression, anxiety, insomnia, and distress, respectively. The analysis showed severe symptoms level of depression for physicians and nurses was 35% and 20% (p < 0.05), respectively. Only three of the independent variables made a unique contribution to the model (gender, profession, and working position) (p < 0.05).Conclusion: COVID-19 pandemic has a significant impact on the mental health of healthcare providers in Saudi Arabia. Female nurses and healthcare providers working in the frontline who were directly treating patients with COVID-19 are at increased risk of severe depression, anxiety and distress.